Development of forward osmosis membrane with nanofiltration-like skin - Chow, Chee Chong. (2011)
Researchers of water treatment field have been extensively studying on forward osmosis (FO) in the recent years due to its main advantage of low or no requirement of external hydraulic pressure for its operation. However, there is currently a lack of a suitable FO membrane that can achieve the same amount of water flux as commercially available reverse osmosis (RO) membranes. Poly (amide–imide) (PAI) hollow fiber membranes with a nano-filtration (NF)-like skin have been developed by the means of simple chemical modifications with polyethyleneimine (PEI) and poly (styrene sulfonate) (PSS) to form positively and negatively charged selective layer respectively. PAI hollow fiber membranes were characterized before and after chemical modification in terms of pure water permeability, molecular weight cut off and salt rejection with MgCl2 and Na2SO4. Hollow fibers presenting high water flux and salt rejection were put to a lab-scale FO filtration setup and its volumetric water flux, JV and corresponding salt flux, JS were measured. FTIR spectroscopy, zeta potential and scanning electron microscope were used to verify the various chemical modifications of the hollow fiber membrane samples.